An Overview of Bicycle Crashes and Injuries in Western Australia - AL Gavin; LB Meuleners; LR Cercarelli; D Hendrie (Journal of Road Safety, 2005)
The aim of this study was to examine the trends in bicycle crashes in Western Australia. Police reports and hospital admissions from the Western Australian Road Injury Database for the period of 1987 to 2000 were analysed. There were 11,114 crashes reported to police involving 11,385 cyclists over the study period. Of these cyclists 81 were fatalities and 1,851 hospitalised. There was a significant decrease in the number of police reported crashes involving cyclists, from 1,012 in 1987 to 612 in the year 2000. The hospital admissions data shows a different trend. Over the study period 9,878 cyclists were admitted to hospital, increasing from 630 in 1987 to 913 in 2000. It was concluded that the use of both police reports and hospital admissions data is crucial to providing an accurate picture of bicyclist crashes. Serious cyclist injury seems to be under-reported in the police data. This is highlighted with the reduction in the number of bicycle crashes reported in the police data, compared to the significant increase in the number of cyclists admitted to hospital.